THE EFFECT OF PRICE, PRODUCT, SERVICE ON ONLINE SHOP SERVICE USER SATISFACTION - Elvina Barutu; Fedita Debyani Siahaan; Kalara Sukmawati Simanjuntak; Hendra Jonathan Sibarani (Faculty of Economic and Business, University of Pasundan, 2022)
This study aims to determine the effect of price, product quality and application service quality on user satisfaction of online shop application services in Medan-Tembung District, this research method uses quantitative descriptive analysis, the population in this study is online shop application service users in Medan-Tembung District. as many as 146,534 people using a sample of 100 respondents, data analysis techniques using the F test, T test and multiple linear regression, it can be seen the magnitude of the influence of variations in user satisfaction of online shop application services in Medan-Tembung District can be seen from the coefficient of determination value is 71.9%. of 28.1% is influenced by other factors such as discount prices and application speed, based on the results of data analysis in this study shows that partially known variables of price, product quality and application service quality partially have a positive and significant effect on user satisfaction of online shop application services. in Medan-Tembung District.